Postnatally Diagnosed Agenesis of Corpus Callosum in Fetuses - Kitova, Tanya Todorova; Kitov, Borislav; Milkov, Denis; Gaigi, Soumeya (Fetal and pediatric pathology, 2014)
Objectives: To examine and characterize the agenesis of the corpus calosum (ACC) in an epidemiological study of fetal autopsies, as well as, to analyze the associated anomalies and to emphasize the importance of the clinical examination of ACC. Methods: The subjects of observation are 20 fetuses from a total of 2238 autopsies carried out during a period of three years (2006-2009) in Tunis. Results: The associated abnormalities are hydrocephalus, cerebellar hypoplasia, agenesis of vermis cerebelli, polymicrogyria and lissencephaly. Sixteen of the cases (80%) are syndromic: Trisomy 13,18,21 (5,1,2 fetuses respectively) and Thanatophoric dysplasia, Fetal akinesia syndrome, Dandy-Walker Malformation and the Association VACTERL are represented by two cases each. Conclusion: The prenatal diagnosis of ACC must be the result of a multidisciplinary approach. The phenotype of the XLAG syndrome creates an interest to study asymptomatic patients with ACC, especially when the anomaly is detected prenatally.